Assessment of the knowledge, attitude and practice of oral hygiene among primary school teachers in Navi Mumbai - Nakhawa, Ojaswee D.; Hindalekar, Manjusha S.; Deshmukh, Ankita V.; Thakkar, Vaibhav P.; Kulkarni, Chinmayee V. (International Journal Of Community Medicine And Public Health, 2021)
Background: School age is an important stage in an individual’s development. Early education of oral hygiene by teachers can cause lifelong benefits to students since teachers are closely involved in children during their developmental stages. Oral diseases are becoming global issues and should be considered of public health importance. Yet, oral diseases are a neglected issue, rarely seen as a priority in health policy. Methods: This study is a descriptive cross-sectional study conducted in primary school teachers from Navi Mumbai, Maharashtra. Total 400 school teachers, selected by stratified sampling technique, had participated in this study. Participants were given self-structured questionnaires with 16 dichotomous questions. Results: 67.5% of teachers expressed that they have never received any demonstrations/lectures in maintaining oral hygiene while 82.8% never had any professional training regarding oral hygiene. For the question, Have you received training by a professional on oral health care and hygiene? teachers with less than 1 year of teaching experience 68.8% responded negatively, 78.8% with 1-5 years of experience reported with ‘no’ and 85.4% and 89.4% were negative responses from teachers with 6-10 years of teaching experience and 11-35 years of teaching experience respectively, showing significant value of p=0.026. Conclusions: From this study we understood that, some degree of awareness is seen in younger aged primary school teachers, but it is not satisfactory, suggesting that teachers still have to undergo training for the same. It is hoped that this survey will help in implementation of training programs.